Oxygen tension modulates extracellular vesicles and its miRNA contents in bovine embryo culture medium. Issue 8 (13th June 2019) - Andrade, Gabriella Mamede; Bomfim, Monalisa Medrado; del Collado, Maite; Meirelles, Flávio Vieira; Perecin, Felipe; da Silveira, Juliano Coelho
Abstract: The biotechnology for in vitro embryo production is becoming increasingly popular, being applied to humans and domestic animals. Embryo development can be achieved with either 20% or 5% oxygen tension. The extracellular vesicles (EVs) are secreted by different cell types and carry bioactive materials. Our objective was to determine the secretion pattern and micro RNA (miRNA) contents of EVs released in the bovine embryo culture environment—embryo and cumulus cell monolayer—on Days 3 and 7 of in vitro culture under two different oxygen tensions: High (20%) and low (5%). The EVs were isolated from the medium and analyzed to determine size, concentration, and miRNA levels. EVs concentration in low oxygen tension increased on Day 3 and decreased on Day 7. Additionally, altered EV miRNAs derived from the embryo‐cumulus culture medium were predicted to regulate survival and proliferation‐related pathways on Days 3 and 7. Moreover, miR‐210 levels decreased in EVs isolated from the culture medium under high oxygen tension suggesting that this miRNA can be used as a marker for normoxia since it is associated with low oxygen tension. In summary, this study provides knowledge of the oxygen tension effects on EVs release and content, and potentially, on cell‐to‐cell communication during in vitro bovine embryo production. Abstract : This study provides knowledge about the role of oxygen tension modulating extracellular vesicles and its miRNAs contents in the bovine embryo culture medium.